(untitled) (Biological Sciences - PJSIR, 1998)
Phytosociological study was carried out over an area of 73780 ha rangelands in southern Attock. The objective of this study was to delineate the existing vegetation into dominant plant communities so as to monitor and maintain the health of these rangelands over time based on floral, edaphic and climatic requirements. Four ecological units were identified and vegetation and landuse map was prepared. Vegetation inventory of Summed Dominance Ratio (SDR) showed a total of 17 plant species in protected unit(sub-unit l.l) and 18 plant species in unprotected unit (sub-unit 1.2) which were distributed among plant communities of Chrysopogon montanus and Heteropogon contortus respectively. Similarly, II plant species in protected unit/sub-unit 2.1) and 12 plant species in unprotected (sub-unit 2.2) were found among plant communities ofAcacia modesta, Acacia nilotica, Adhatoda vesica and Ochthochloa compressa, respectivly. Overall the invader plant species, which were high in unprotected area were being replaced with desirable forage tree and grass species in protected areas.